IWRM and the legacies of large-scale agriculture in the Peruvian Amazon (Alternautas, 2022)
The advancement of agribusiness in Latin America has created environmental strains and les to increasing conflicts with local based economies dependent on small scale agriculture. Among the efforts to halt its negative effects, new models of resource governance emerged aiming to integrate stakeholders and users into accountable organisations. This article reviews the attempt to impose Integrated water resources management (IWRM) over the water governance arrangements of a native community in the Peruvian Amazon that faces an increasing intervention of rice agribusiness in their lands. The resulting dynamic can be understood as an altered arrangement: it doesn’t lead to the creation of an IWRM institution, nor does it reject new governance architectures. The rescaling of water governance, the interpretation of IWRM meanings and the contingency of the results, all within the frame of a history of agricultural development interventions in indigenous lands, helps us understand this phenomenon.